Putting Social Justice in Social Work Education with Inquiry-Based Learning. Issue 5 (19th October 2020) - Archer-Kuhn, Beth
ABSTRACT: This paper situates inquiry-based learning (IBL) in a post-secondary context while examining possibilities for social work education and practice. Specifically, in what ways has IBL been utilized in higher education, and how might IBL be compatible with social work values that promote social justice? This paper begins with a brief overview of the definitions of IBL and associated theory, then illustrates the benefits of the approach and varying experiences of its application, and finally considers how IBL and social work are complementary insofar as IBL upholds various social work principles and supports the linking of theory to practice during service-learning.